Exploring BIPA Teachers' Experiential Learning Practices in Cultural Immersion for Introducing Minangkabau Culture to International Students - Vivi Indriyani; Delsy Arma Putri; Hanifah Yulia Sari; Indah Muzdalifah; Suhailee Sohnui (Jurnal Pemberdayaan Masyarakat, 2026)
Cultural integration in teaching Indonesian for Foreign Speakers (BIPA) was recognized as a crucial element for developing authentic intercultural competence, particularly in addressing sociocultural adaptation challenges faced by international students. Although the immersion method had been widely acknowledged as a transformative approach, its practical implementation in connecting experiential learning theory with local cultural wisdom still required deeper exploration. Therefore, this study examined the experiential learning practices of BIPA teachers in utilizing cultural immersion to introduce Minangkabau culture to foreign learners in West Sumatra. A mixed-methods approach with a descriptive design was employed. Quantitative data were collected from 48 BIPA teachers through a structured Likert-scale questionnaire, while qualitative data were obtained from observation sheets based on learning practice videos. The data were analyzed using descriptive statistics and qualitative analysis to provide a comprehensive understanding of teaching practices. The findings indicated that experiential and cultural immersion-based BIPA learning had been implemented effectively through structured planning, authentic cultural activities, and the integration of language and culture in real-life contexts. Teachers demonstrated highly positive perceptions of this approach, as reflected in strong student engagement, reflective learning processes, and active language use. However, challenges related to time constraints, limited facilities, and uneven student participation remained evident, suggesting the need for further optimization.